Oral mark in the application of an individual identification: From ashes to truth - Anshul Chugh; Anumeha Narwal (Journal of Forensic Dental Sciences, 2017)
Forensic odontology is the branch of dentistry which deals with the proper handling, examination, evaluation and presentation of dental findings in the interest of justice. After major disasters and perimortem assaults such as earthquakes, fires, severe head and neck trauma or gross decomposition, accurate and early identification of dead and injured becomes important. In the absence of other records in such cases, identification is based on restorations, missing teeth and prosthetic devices such as partial and complete removable/fixed prosthesis or implant retained devices. This brings out the major role of prosthodontics to investigate the identity of suspects in the criminal cases as well as the deceased human beings in traumatic injuries or in disasters. Denture identification systems are being used as means of postmortem identification of edentulous persons which has evolved from the inclusion of some form of printed label in a denture to more high-tech methods. The provision of implant retained complete lower denture, antemortem, and postmortem radiographs of edentulous persons and correlation of bite marks using special impression techniques provide another potential source of evidence for human identification. Hence, this literature review throws some light on the role played by prosthodontist in forensic odontology.